Health Literacy and Hearing Healthcare Use. (11th December 2020) - Tran, Emma D.; Vaisbuch, Yona; Qian, Z. Jason; Fitzgerald, Matthew B.; Megwalu, Uchechukwu C.
Abstract : Objective: To assess whether health literacy is associated with: 1) degree of hearing loss at initial presentation for audiogram and 2) hearing aid adoption for hearing aid candidates. Methods: We identified 1376 patients who underwent audiometric testing and completed a brief health literacy questionnaire at our institution. The association between health literacy and degree of hearing loss at initial presentation was examined using linear regression, adjusted for age, gender, marital status, education level, race, language, employment status, and insurance coverage. The association between health literacy and hearing aid adoption was examined in the subset of patients identified as hearing aid candidates using logistic regression, adjusted for demographic factors and insurance coverage. Results: Patients with inadequate health literacy were more likely to present with more severe hearing loss (adjusted mean pure‐tone average [PTA] difference, 5.38 dB, 95% confidence interval [CI] 2.75 to 8.01). For hearing aid candidates (n = 472 [41.6%]), health literacy was not associated with hearing aid adoption rate (odds ratio [OR] 0.85, 95% CI 0.40 to 1.76). Hearing aid coverage through Medicaid (OR 2.22, 95% CI 1.13 to 4.37), and moderate (OR 2.70, 95% CI 1.58 to 4.69) or moderate–severe (OR 2.23, 95% CI 1.19 to 4.16) hearing loss were associated with hearing aid adoption. Conclusions: In our population, patients with low health literacy are more likely to present with higher degrees of hearing loss, but no less likely to obtain hearing aids compared with patients with adequate health literacy. Hearing loss severity and hearing aid coverage by insurance appear to be the main drivers of hearing aid adoption. Level of Evidence: 3 Laryngoscope, 131:E1688–E1694, 2021